New sources of powdery mildew resistance among winter bread wheat for adjusting the breeding immunological programs in the Agricultural Research Center “Donskoy” - Т. G. Derova; N. V. Shishkin; О. S. Kononenko (Зерновое хозяйство России, 2021)
Systematic work on the development of winter wheat varieties possessing resistance to a complex of the most harmful diseases has been carried out in the Agricultural Research Center “Donskoy” since the early 1970s. During this period, there has been created a large number of varieties that possess resistance to 3–4 diseases in conditions of infectious backgrounds of pathogens. Due to the analysis of varieties, there was identified a small number of varieties resistant to powdery mildew. Powdery mildew, caused by the fungus Blumeria graminis (DC) Speer, annually occurs on wheat, affecting all aboveground plant organs. Earlier the FSBSI “ARC “Donskoy” developed and widely cultivated the medium-resistant varieties ‘Tanais’ (2006), ‘Nakhodka’ (2015), ‘Etyud’, ‘Shef’, ‘Lilit’ (2016), ‘Volnitsa’ (2017), ‘Polina’, Yubiley Dona’ , ‘Podarok Krymu’ (2018), ‘Niva Dona’ (2019). In recent years, breeders have developed such varieties with high resistance to the pathogen as ‘Donskaya Step’ (2016), ‘Premiera’, ‘Univer’ (2018), ‘Priazovye’, ‘Zolotoy Kolos’ (2020). But the breeding process of varieties for resistance to powdery mildew is difficult, since it is explained by the small number of effective resistance genes and their sources. Therefore, the purpose of the current study was to identify new sources of resistance to the pathogen. Under the conditions of artificial infection, during last 10 years there was conducted a testing of 302 varieties and samples of winter wheat of domestic and foreign breeding. There have not been identified immune varieties. There was identified a small percentage (15.2) of varieties that were resistant to the pathogen. Among the Russian varieties they were ‘L 3191 k-5-8’, ‘Akhmat’, ‘Alievich’, ‘Barier’, ‘Ulyasha’, ‘Knyaginya Olga’, which were not attacked by the disease over the years of testing. Among foreign varieties, the varieties ‘Bombus’, ‘Sailor’ (France), ‘Etana’, ‘Rotax’, ‘KVS-Emil’ (Germany), ‘Fidelius’ (Austria), ‘MV 09-04’ (Hungary) were identified as the best ones in their resistance to powdery mildew. All identified sources of resistance have been recommended in breeding programs for immunity.